2020
DOI: 10.1155/2020/1346340
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Nomograms for Primary High‐Grade Glioma Patients in Adult: A Retrospective Study Based on the SEER Database

Abstract: Purpose. In our study, we aimed to screen the risk factors that affect overall survival (OS) and cancer-specific survival (CSS) in adult glioma patients and to develop and evaluate nomograms. Methods. Primary high-grade gliomas patients being retrieved from the surveillance, epidemiology and end results (SEER) database, between 2004 and 2015, then they randomly assigned to a training group and a validation group. Univariate and multivariate Cox analysis models were used to choose the variables significantly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…Pignatti [41] de ned high-risk patients with low-grade glioma as the largest diameter of the tumour ≥ 6 cm, and Gorlia [42] suggested that the numerical value was accurate to 5cm. Then the value was rapidly lowered to 2.6cm in patients with high-grade gliomas [43]. Taken together, it is more reasonable than the value was determined to be 4.9cm by our research and the value would make the parameter more suitable to serve as a prognostic and/or predictive factor for LGGs.…”
Section: According To Our Nomograms Age At Diagnosis Was Con Rmed Asmentioning
confidence: 60%
See 2 more Smart Citations
“…Pignatti [41] de ned high-risk patients with low-grade glioma as the largest diameter of the tumour ≥ 6 cm, and Gorlia [42] suggested that the numerical value was accurate to 5cm. Then the value was rapidly lowered to 2.6cm in patients with high-grade gliomas [43]. Taken together, it is more reasonable than the value was determined to be 4.9cm by our research and the value would make the parameter more suitable to serve as a prognostic and/or predictive factor for LGGs.…”
Section: According To Our Nomograms Age At Diagnosis Was Con Rmed Asmentioning
confidence: 60%
“…Many previous studies have shown the accurate predictive ability of nomograms for predicting overall survival in patients with low-grade endometrial stromal sarcoma [10], adrenocortical carcinoma [15], hepatoblastoma [16], and many other system cancers. So far, only a few sporadic studies have investigated the straightforward application of nomograms in glioma based on the SEER database [17][18][19][20]. WHO grade II/III glioma is a relatively rare tumour, with no individualized prognostic predictive tool to manage follow-up and aid accurate prognostic assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of glioma, pediatric and adult patients exhibited apparent epidemiological and biological characteristics distinctions between and within different WHO grades (Shaw and Wisoff, 2003;Diwanji and Engelman et al, 2017;Zapotocky and Ramaswamy et al, 2018;Jiang and Yang et al, 2019). Tools for predicting the prognosis of adult low-grade and high-grade glioma have been well developed (Zhao and Chen et al, 2019;Yang and Yao et al, 2020), but there was inadequate clinical evidence on the prognosis of pediatric LGGs. Therefore, we developed a prognostic nomogram in the current study to predict pediatric patients' prognosis with LGGs using the data derived from the SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…Recognized risk factor for GBM is exposure to ionizing radiation, and it can be potentially altered [7]. Additionally, several studies have explored the factors that affect the overall survival and prognosis of GBM, including age at diagnosis, sex, surgery, radiotherapy and chemotherapy, etc [8][9][10][11]. Prognostic factors to predict diseases-speci c survival (DSS) of patients are generally less studied.…”
Section: Introductionmentioning
confidence: 99%